TEACHING VOCABULARY BY USING WORD BASEBALL GRAPHIC ORGANIZER TO THE ELEVENTH GRADERS OF SENIOR HIGH SCHOOL - Nirwana, Dian; Wahyuni, Sri (ELT Forum: Journal of English Language Teaching, 2017)
This paper is based on a research which examined the eleventh graders’ achievement in vocabulary mastery. The study aimed to find out the significant difference of students’ vocabulary achievement between the students who were taught by using word baseball graphic organizer and those who were not and to investigate the effectiveness of using word baseball graphic organizer to teach vocabulary. The study adopted quasi-experimental non-equivalent control group design. The data were gained through pre-test and post-test scores and participants’ responses of the questionnaire. The results of the study showed that the mean score of the pre-test in the experimental group was 74.35, while in the control group was 74.62. In the post-test, the mean score of the experimental group was 83.09, and the control group was 79.29. The result of post-test increased. In addition, the t-test result was 1.990, and t-table was 1.787. It can be clearly seen that tvalue is higher than ttable. It means that the hypothesis of H1 was accepted and H0 was refused. According to the proven hypotheses, I can conclude that teaching vocabulary using word baseball graphic organizer was proven to be effective for the eleventh grade students of senior high school.